SARANA ISLAMISASI DI JAWA ABAD XV MENURUT BABAD GRESIK - Ulum Fasih (Batuthah: Jurnal Sejarah Padaban Islam, 2022)
Babad Gresik as a traditional historiography contains important narratives about the spread of Islam by preachers. It is told in the Chronicle that the spread of Islam began in the 14th century and was carried out in Gresik by means of trade propaganda. In the 15-16th century, the spread of Islam became more massive, not only limited to Gresik, but Java in general, using different means of preaching than in the 14th century. This paper has a purpose which wants to answer the problem of changing the means of da'wah from trade in the 14th century to marriage in the 15th century. The analytical method that is used in this research is descriptive qualitative analysis with literature study techniques. The result of this research is there is a change of islamization in Java. In 15AD the spread of islam was done through marriage which has been started by Syekh Maulana Ishaq. The cause of this change is that Gresik harbor was continuously losing its existence, so the spread of islam will be ineffective if they keep using trading way.